Horse Races and Polo Games of Mongolians (Tartars)
panel #2, detail: 5 men playing vigorous polo. Imperial Benedictine Abbey of Sts. Stephen and Vitus. founded by Benedictine monks from abbey of Corvey on the Somme, France. This developed in 9th & 10th c. as a very important cultural center in Northern Europe. UNESCO nominee